Evaluation of antioxidant effect of various Extracts of leucasaspera in vitro - K.G.KRIPA,; D.CHAMUNDEESWARI, (International Journal of Pharma and Bio Sciences, 2016)
Lamiaceae herbs known for their culinary properties are a rich source of potentially health-beneficial antioxidant polyphenols. The objective of this investigation was to evaluate and prove the in vitro antioxidant activity of five different extracts of aerial parts of the plant Leucas aspera, belonging to the family Lamiaceae on different models namely the DPPH free radical scavenging assay, Fe2+- ascorbate induced lipid peroxidation, Nitric oxide scavenging activity, Total antioxidant equivalence and Hydroxyl radical scavenging activity by standardized methods. The results showed the ethanolic and hydroalcoholic extracts of Leucas aspera (EELA and HAELA) to exhibit maximum inhibition of free radical formation followed by EAELA, the ethyl acetate extract. The least antioxidant potential was exhibited by HELA and CELA, the n-hexane and chloroform extracts of Leucas aspera. The potential antioxidant activities in vitro may indicate their therapeutic and related beneficial properties in oxidative stress, a condition underlying many disorders.